Audio Branding Yearbook 2013/2014: ((( ABA ))) Audio Branding Academy - Bronner, Kai; Hirt, Rainer; Ringe, Cornelius (Nomos Verlagsgesellschaft mbH & Co. KG, 2014)
After previous events in Hamburg, New York and Oxford, the Audio Branding Congress 2013 took place in Moscow. The Audio Branding Academy organized the event in cooperation with the Higher School of Economics Moscow, the Humboldt University Berlin and its Russian partner DigiSky.According to the motto „Sound Opportunities“, technological trends as well as the conditions for the development of new business in the Russian market were being discussed by experts from 15 countries. Furthermore, the Audio Branding Award 2013 was given to the best practice cases presented at the Congress.This Yearbook includes articles of the best practice cases from the Audio Branding Award, contributions from the scientific Call for Papers, a documentation of the market survey Audio Branding Barometer 2013, results of a study, analysing 300 top brands in 10 countries with regards to their use of music and sound as well as articles about current developments and opportunities in the audio branding industry.